PENGARUH BIMBINGAN KONSELING GURU PENDIDIKAN AGAMA KRISTEN TERHADAP PERKEMBANGAN KEPRIBADIAN SISWA - Bangun Munte; Darman H. Samosir (Jurnal Dinamika Pendidikan, 2018)
ABSTRACT This research aims to find out what extend the effect of counseling guidance for the teacher of Christian religious education in to the character development at school. The research sample is 50 students which have been selected from population. This research applies descriptive method. Then to analyze the data in this hypothesis research uses Pearson product moment by giving questionnaires to measure variable X (the effect of counseling guidance to teacher of Christian religious education) and variable Y (the studentsâ€™ development character). The research finding shows that correlation (r) 0.43 with determination test is 18.49% and to know whether significant or not the correlation of real level (Î±) = 0,05, so â€˜tâ€™ test is applied by the criteria of testing, if â€œtâ€ which is gained more that ( > ) from â€œtâ€ table pada level significant 1 â€“ 0,05 with dk = k â€“ 2 so the alternative hypothesis (Ha) is received while nul hypothesis (H0) is rejected. The result from the data analysis found that â€œtâ€ test (>) â€œtâ€ tabel = 3.27 ( > ) 1,68, so alternative hypothesis is received. From the analysis result, it can be concluded that there is significant effect of counseling guidance for the teacher of Christian religious education in to the character development at school.Key Words: Conunseling Guidance, Studentsâ€™ Development Character ABSTRAK Tujuan penelitian ini adalah untuk melihat sejauhmana Pengaruh Bimbingan Konseling Guru Pendidikan Agama Kristen terhadap Perkembangan Karakter siswa di sekolah. Jumlah sampel yang diambil dari populasi sebayak 50 orang. Penelitian ini menggunakan metode deskriptif, sedangkan analisa data yang dilakukan dalam penelitian hipotesis adalah kolerasi product moment pearson dengan alat pengumpulan data adalah angket untuk Variabel X (Pengaruh Bimbingan Konseling Guru Pendidikan Agama Kristen) dan Variabel Y (Perkembangan Karakter siswa). Dari hasil pengujian diperoleh pengujian kolerasi (r) 0,43 dengan uji determinasi sebesar 18,49% dan untuk mengetahui signifikan tidaknya koefisien kolerasi pada taraf nyata (Î±) = 0,05 maka diadakan uji â€œtâ€ dengan kriteria pengujian jika t hitung yang didapat dari perhitungan lebih besar ( > ) dari t tabel pada taraf signifikan 1 â€“ 0,05 dengan dk = k â€“ 2 maka hipotesis diterima dan dalam hal lain ditolak. Dari hasil pengujian diperoleh diperoleh t hitung ( > ) t tabel = 3,27 ( > ) 1,68, maka hipotesis diterima. Dengan demikian dapat dikemukakan berpengaruh yang berarti antara Pengaruh Bimbingan Konseling Guru Pendidikan Agama Kristen terhadap Perkembangan Karakter siswa di sekolahKata Kunci: Bimbingan Konseling dan Perkembangan Karakter siswa